2-Amino-5-phenyl-1,3,4-thiadiazole at 110 K - Öztürk, S; Akkurt, M; Cansiz, A; Koparir, M; Sekerci, M; Heinemann, FW (Int Union Crystallography, 2004)
The crystal structure of the title compound, C8H7N3S, previously determined at room temperature [Ishankhodzhaeva, Kadyrova, Surazhskaya, Parpiev & Koz'min (2001). Zh. Org. Khim, 37, 759-761], has been redetermined at 110 K. Comparison of the two structures reveals significant differences in the unit-cell parameters, while the molecular geometry and hydrogen-bonding network are essentially the same in both structures.
Keywords: Crystal